2006
DOI: 10.4049/jimmunol.176.10.6172
|View full text |Cite
|
Sign up to set email alerts
|

Immature Human Dendritic Cells Infected with Leishmania infantum Are Resistant to NK-Mediated Cytolysis but Are Efficiently Recognized by NKT Cells

Abstract: Dendritic cells (DC) play an important role in innate and adaptive immunity, interacting with T cells, NK, and NKT cells. A critical step in the interaction of the parasitic protozoa Leishmania with their host is the evasion of both innate and adaptive immunity, producing a long-lasting chronic infection. There is growing evidence that these parasites can modify the Ag-presenting and immunoregulatory functions of DCs. The cells and mechanisms involved in innate immune response against Leishmania are still poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…These include (i) the application of IL-2-activated killer (LAK) cells without further phenotypic characterization (55) Thus, on the basis of our own in vitro and in vivo results, we argue that highly purified NK cells do not exert a cytolytic effect against infected macrophages in vitro, except for the small degree of lysis already seen with uninfected cells. This notion is further supported by the observation that human immature DCs infected with L. infantum were resistant to NK cell-mediated lysis due to the upregulation of HLA-E (a ligand for the inhibitory NK cell receptor CD94/NKG2A) (10) and that LAK cells also failed to lyse mouse macrophages infected with the related pathogen Trypanosoma cruzi (79).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These include (i) the application of IL-2-activated killer (LAK) cells without further phenotypic characterization (55) Thus, on the basis of our own in vitro and in vivo results, we argue that highly purified NK cells do not exert a cytolytic effect against infected macrophages in vitro, except for the small degree of lysis already seen with uninfected cells. This notion is further supported by the observation that human immature DCs infected with L. infantum were resistant to NK cell-mediated lysis due to the upregulation of HLA-E (a ligand for the inhibitory NK cell receptor CD94/NKG2A) (10) and that LAK cells also failed to lyse mouse macrophages infected with the related pathogen Trypanosoma cruzi (79).…”
Section: Discussionsupporting
confidence: 58%
“…Several studies suggested that NK cells also exert cytolytic effects against host cells infected with nonviral pathogens (1,47,53,55,74). On the other hand, both viral and nonviral infections exist in which host cells acquire resistance to NK cell lysis (10,20,21,40). However, even without host cell lysis, NK cells might still operate as cytotoxic effectors, either by direct killing of extracellular microbes or by inducing the death of intracellular pathogens via the transfer of perforin or granulysin (1,25,42,45,52,68,75).…”
mentioning
confidence: 99%
“…4B). Campos-Martin et al (40) have shown that infection of human monocyte-derived DCs with Leishmania infantum results in up-regulation of surface CD1d and efficient recognition and killing of these infected DCs by NKT cells. However, we found no obvious effect of L. major lysate on DC maturation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In some infections, such as Leishmania, their cytotoxicity may be essential to fight the infection. Indeed dendritic cells infected with L. infantum up-regulate CD1d cell surface expression and consequently can be efficiently recognized and killed by iNKT cells [85]. Interestingly, such cytotoxicity is increased by IL-4 in an autocrine fashion [83].…”
Section: Inkt Cell Cytotoxicitymentioning
confidence: 98%